MODEL INTERNALISASI DIMENSI BERKEBINEKAAN GLOBAL MELALUI PROYEK `````````"PASAR MINI NUSANTARA" DI TK AL MUHAJIRIN KABUPATEN PURWAKARTA - Rosa, Ade TR; Maulana, Bagja; Susanti, Hetty; Kosirin, Iis; Mulyash (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to design, implement, and evaluate an internalization model of the Global Diversity dimension through the "Pasar Mini Nusantara" project within the framework of the Pancasila Student Profile Strengthening Project (P5) at TK Al Muhajirin, Purwakarta Regency. In the Society 5.0 era, young children face significant digital exposure that often sparks early ethnocentrism and lessens social empathy. Using a qualitative case study approach, data were gathered from the school principal, group B teachers, and 20 children through participant observation, in-depth interviews, and thematic documentation. The results indicate that the structured internalization model, running through stages of cultural transformation, transaction, and transinternalization, successfully builds tolerant habits, eliminates early peer-mockery regarding physical or dialect differences, and promotes queueing discipline. Active involvement of parents representing regional booths proved vital in making cultural values tangible. This study concludes that an experiential-learning-based project with cultural-economic themes offers an alternative, practical strategy for early childhood character growth.